Experimental and numerical analysis on masonry arch built with fictile tubules bricks. (December 2018) - Scuro, Carmelo; Lamonaca, Francesco; Codispoti, Rosamaria; Carnì, Domenico Luca; Olivito, Renato S.
Highlights: Experimental test was conducted on scale model in fictile tubules bricks to determine its mechanical characteristics. Analytical model is proposed able to investigate the load that induce the develop of first crack. It is demonstrated that the rule of mixture can be applied to provide a first homogeneous elastic module. The damage model of Mazars was calibrated for a historical mortar. Abstract: Numerous archaeological discoveries made all over the Mediterranean area have highlighted the use of a particular building technique based on fictile tubules bricks. This building technique was commonly used for the building of walls and domes in thermal baths and masonry kilns since the Roman Empire. This paper investigates the behavior of structures employing such technology via experimental tests and numerical analysis. In order to obtain the value of force that induced in the structure the develop of the first cracks, a masonry scale arch was built and tested in the laboratory of University of Calabria. After that, numerical and analytical models were performed to verify and validate the experimental results obtained.